2018
DOI: 10.7567/apex.11.034103
|View full text |Cite
|
Sign up to set email alerts
|

True-blue laser diodes with tunnel junctions grown monolithically by plasma-assisted molecular beam epitaxy

Abstract: We demonstrate true-blue 450 nm tunnel junction (TJ) laser diodes (LDs) grown by plasma-assisted molecular beam epitaxy (PAMBE). The absence of hydrogen during PAMBE growth allows us to achieve TJs with low resistance. We compare TJ LDs with LDs of standard construction with p-type metal contact. For both types of LD, the threshold current density is around 3 kA/cm 2 and the slope efficiency is 0.5 W/A. We do not observe any significant changes in optical losses and differential gain in TJ LDs compared with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Upper cladding is a 500 nm p-type GaN with Mg doping concentation of 1 × 10 18 cm −3 . This is followed by a TJ [16] capped with GaN:Si contact layer. Two sets of samples were realized with different designs of EBL.…”
Section: Methodsmentioning
confidence: 99%
“…Upper cladding is a 500 nm p-type GaN with Mg doping concentation of 1 × 10 18 cm −3 . This is followed by a TJ [16] capped with GaN:Si contact layer. Two sets of samples were realized with different designs of EBL.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the effects of using TJ structure [22][23][24][25], and to further analyze the carrier transport and distribution within the MQW active region of the InGaN-based VCSELs, an advanced simulator PICS3D was utilized in this specific study. The PICS3D is based on three-dimensional finite element analysis and can deal with the optical and electrical properties of optoelectronic devices by solving Poisson's equation, current continuity equations, carrier transport equations, complex wave equations, and photon rate equations.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…In PAMBE, hydrogen is not incorporated into GaN:Mg layers, therefore there is no passivation of Mg dopant and no need for post-growth annealing. For this reason, PAMBE seems to be much better suited than MOVPE for practical realization of the vertical devices with buried p-type layers [14]. Recently, making use of PAMBE, it was shown that TJs' resistance for wide bandgap semiconductors can be significantly reduced by making use of the piezoelectric fields in the region of the junction [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, making use of PAMBE, it was shown that TJs' resistance for wide bandgap semiconductors can be significantly reduced by making use of the piezoelectric fields in the region of the junction [3,7]. The use of piezoelectric fields and heavy pand n-type doping levels allowed us to reduce the TJs' resistance to a level appropriate for a demonstration of the continuous wave operation of nitride laser diodes (LDs) [14].…”
Section: Introductionmentioning
confidence: 99%